Changes in major psychiatric disorders in children and adolescents from 2001 to 2020: A retrospective single-center study - Zheng, Hongyu; Jiang, Xiaolu; Yang, Rong; Wang, Shuo; Zhong, Hui (Frontiers in Psychiatry, 2023)
Objective: This study aimed to determine the hospitalization rates, length of stay, age at the time of admission, and sex distribution for major psychiatric disorders in children and adolescents and provide a reference for early intervention for these diseases and distribution of medical resources in hospitals. Methods: We screened 4,423 patients in the child and adolescent wards of the Anhui Provincial Mental Health Center from 2001 to 2020, and examined the top four (81.1%) mental health disorders that accounted for the overall proportion of patients admitted, namely schizophrenia (SCZ) (45.7%), depressive disorder (DD) (14.5%), bipolar disorder (BD) (9.3%), and childhood emotional disorder (CED) (11.6%), and for each disorder, the percentage of hospitalization, length of stay, age at admission, and sex distribution were analyzed. Results: From 2001 to 2020, there was a significantly decreasing trend in the proportion of hospitalizations for SCZ (p<0.001) and an increasing trend for depression and CED (p<0.001). In terms of length of stay, SCZ was significantly longer than the other three disorders (p<0.001), whereas there was no significant difference between DD, BD and CED, and there was no significant trend in length of stay for any of the four disorders. The age at admission for CED was significantly lower than that for the other three disorders (p<0.001). There was a decreasing trend in the age at admission for DD (p=0.011) and an increasing trend for BD (p=0.001). A significant increase in the number of female patients admitted for SCZ, DD, and CED was observed, while there was no significant change in the sex ratio for BD. Conclusion: Although there is a significant downward trend in the percentage of hospitalizations for SCZ, it is still the most common psychiatric disorder in children and adolescents. We observed a significant increase in the percentage of hospitalizations for DD and CED. In addition, the proportion of female patients being hospitalized is on the rise, and this aspect requires continuous attention.